Blepharoptosis: Pattern and its Surgical Management in a Tertiary Eye Hospital of Eastern Nepal - Arjyal Kafle, Prerna; Hamal, Diwa; Sahu, Sabin; Chaudhary, Sharmila (Nepalese Medical Journal, 2022)
Introduction: Blepharoptosis or drooping of the eyelid is a common disease entity presenting in oculoplasty department. Depending on its severity it causes visual disturbances as well as cosmetic problems. Appropriate management and timely surgical intervention results in a good outcome. Materials and methods: This is a hospital-based study of a blepharoptosis patient that presented in the Oculoplasty department and underwent ptosis correction by various methods from July 2016- December 2019. Results: A total of 85 cases with 104 eyes underwent ptosis surgery. The mean age was 24.5 years. Among them, 31.8% were pediatric and 68.2% were adults. Astigmatism was seen in 21.1% followed by myopia in 10.6% and hypermetropia in 4.7%. Amblyopia was seen in 13% of cases. Common surgical procedures performed were frontalis sling suspension 64.7%, followed by levator advancement 33%, and frontalis sling surgery with V-Y plasty 2.3%. Conclusions: Ptosis is seen to be associated with refractive errors, strabismus, or amblyopia. Proper clinical evaluation of the patient is essential to know the etiology, type, and severity of ptosis. Timely surgical intervention is necessary to prevent morbidity and enhance its outcome.